Empirical study on relationship between informatisation and development of tourism in China. (1st January 2012) - Yao, Lifen; Long, Ruyin; Li, Qingchen
The relationship between informatisation and tourism tops the agenda of the economics research. In this paper, cointegration analysis, error correction model, and Granger causality estimation were used to test the relationship of China's informatisation and tourism, based on the data from 1994 to 2010. The empirical test showed that although the short-run fluctuation exists, there is a stable equilibrium relation between China's informatisation and tourism in the long run. In addition, on the comparison between international and domestic tourism, it concluded that the informatisation plays more significant role in promoting domestic tourism than international tourism.